Review of potter wasps with a petiolate metasoma excluding so-called "Zethinae" (Hymenoptera: Vespidae: Eumeninae) in the Lesser Sunda Islands of the Indonesian Archipelago - Nugroho, Hari; Kojima, Jun-Ichi; Ubaidillah, Rosichon (Zootaxa, 2013)
Twenty species and six subspecies of nine genera of eumenine wasps with a petiolate metasoma occurring in the Lesser Sunda Islands are listed. New synonymies are proposed for Delta campaniforme campaniforme (Fabricius 1775) (=D. campaniforme gracilior Giordani Soika 1986, syn. nov.) and D. nigriculum Giordani Soika 1986, stat. nov. (=D. campaniforme rendalloide Giordani Soika 1993, syn. nov.). Eumenes piriformis de Saussure and E. inconspicuus Smith are newly recorded from the Lesser Sunda Islands; E. pius Giordani Soika, D. nigriculum Giordani Soika, D. pyriforme (Fabricius), D. sciarum (van der Vecht), Pareumenes nigerrimus van der Vecht, and Labus vandervechti Giordani Soika, are newly recorded from some islands of the Lesser Sunda. Hitherto unknown male of P. nigerrimus is described.